(untitled) - Madelung, Wilferd (Cambridge, 1996)
In a convincing reinterpretation of early Islamic history, Wilferd Madelung examines the conflict that developed after the death of Muhammad for control of the Muslim community. He demonstrates how this conflict, which marked the demise of the first four caliphs, resulted in the lasting schism between Sunnite and Shi'ite Islam. In contrast to recent scholarly trends, the author takes up the Shi'i cause, arguing in defense of the succession of 'Ali. This book will make a major scholarly contribution to the debate over succession.
Keywords: Caliphate,Islamic Empire,Islam,Hồi giáo,Đế chế Hồi Giáo,Đế chế Hồi Giáo; History,Kings and rulers,Succession,History,Lịch sử,Vua và cai trị,Kế thừa,Lịch sử